VO#044 The quotation for RCC bench & floor joints at stair - BUCG-ABC Joint Venture (BUCG-ABC JV) (2023)
This record consists of general correspondence regarding the submission of price quotation for RCC bench and floor joints at stair of BRACU new campus building.